CGIAR research through an equality and empowerment lens - Pyburn, Rhiannon; Eerdewijk, Anouka van (International Food Policy Research Institute, 2021)
Over the past decade or so, there has been a renewed, and more concerted and comprehensive, interest in gender equality and women’s empowerment in the agricultural development sector. Renowned development organizations have put gender dynamics back in the spotlight by means of a series of publications focused on gender equality. This momentum has generated a unique opportunity to advance gender equality within and through agricultural research and development, and to institutionalize gender research within agricultural research for development (AR4D) organizations. This has also given us a chance to ask whether enough traction has been gained to mark a true turning point. As one key thinker in this field has stated that, “with agriculture now firmly back on the development agenda, it is time to re-socialize the ways that agricultural research, and practice deal with women and men, and analyze them both in relation to one another and their wider context” (Okali 2012, 2). This book is both an expression and a consequence of this overall momentum.